Machinery prognostics and prognosis oriented maintenance management - Yan, Jihong (Wiley, 2014)
"This book gives a complete presentation of the basic essentials of machinery prognostics and prognosis oriented maintenance management, and takes a look at the cutting-edge discipline of intelligent failure prognosis technologies for condition-based maintenance. Latest research results and application methods are introduced for signal processing, reliability moelling, deterioration evaluation, residual life prediction and maintenance-optimization as well as applications of these methods"--